ASSA13-04-1 The Study of Acute Intravenous Saline Load Test Replacement Preoperative Hydration For Screening and Prevention of Contrast Induced Nephropathy. (29th April 2013) - Yong, Xia; Wen-juan, Liu; Ying, Shen
Abstract : Background: Contrast induced nephropathy (CIN) is the third most common cause of acquired acute kidney injury. People with blood pressure of salt sensitive (SS) has genetic kidney natriuresis defects. SS has gained increasing clinical attention because of the possible association of SS with the risk of developing cardiovascular and renal complications. Therefore, the SS more susceptible to CIN is worth of studying. Hydration is the earliest used, widely accepted and effective method to reduce CIN. Previous study showed that 0.9% NaCl is better than 0.45% NaCl in reducing CIN by intravenous hydration. What's more, 1.0% NaCl saline load test in CIN prevention is worth of studying. Objective: To identify the new risk factors of CIN and to prevent CIN by using acute intravenous saline load test instead of preoperative hydration. Methods: Total 240 patients receiving CAG and/or PCI and belonging to medium- and high-risk according to the CIN risk scores were recruited. The simplified saline load test was done before operation in 160 patients. Conventional intravenous infusion total 9.0 ml/kg of 1.0% NaCl continued 8 hour's time. Use the cuff method measuring blood pressure before and after the infusion, calculating the average blood pressure according to the formula = 1/3 systolic blood pressure +2/3 diastolic blood pressure, the average blood pressure after infusion higher than before ≥ 5mmHg is SS (SS group n = 88), otherwise is not salt sensitive (NS group, n = 72). The control group including 80 patients who has not received saline load test before operation (control group, n = 80). All patients in the three groups receive hydration with 0.9%NaCl continued 24 hour's time. The heart function index (NT-proBNP), renal function index (Scr, BUN) at postoperative 24 h, 48 h, 72 h and the urinary NGAL at postoperative 2 h, 4 h, 6 h, 12 h, 24 h, 48 h, 72 h were collected and analysed. Results: The incidence of CIN in the control group was significantly higher than that in SS group (17.50% vs 12.50%, p < 0.01) and NS group (17.50% vs 1.38%, p < 0.01). The incidence of CIN in the SS group was also significantly higher than that in the NS group (12.50% vs 1.38%, p < 0.01). The heart function in the NS group after CAG and/or PCI was better than that in the NS group (p < 0.05). But the time in hospital and the rate of adverse reaction during hospitalisation were no significant difference in the three groups (p > 0.05). Conclusions: SS could be one of new risk factors of CIN. The acute intravenous saline load test could replace preoperative hydration, screening and preventing the CIN.